Prediktor Kualitas Hidup pada Musisi - Retha Arjadi; Christ Billy Aryanto; Vanessa Arieputri (MANASA, 2021)
Musical activities carried out by musicians can bring benefits but can also cause discomfort to theextent of causing mental health problems. This condition in general can be reflected through thequality of life of the musicians. The participants of this study were 70 musicians with the agerange of 18-47 years old (Mean=27.94, SD=6.73), and was obtained through accidental sampling.This study aims to examine the predictor role of sex, age, music playing duration, music educationduration, and length of practice per day, on the quality of life of the musicians. Multiple regressionanalysis showed significant results (R2=0.185, F(5,64)=2.907, p<0.05). Predictors thatspecifically significant predicting the quality of life of the musicians are sex, age, and musiceducation duration. Male musicians were reported having a higher quality of life (Mean=89.97,SD=12.60) than the female musicians (Mean=83.97, SD=8.48). The higher the musicians' agesand education duration also predict the higher quality of life. The limitations of this research andrecommendations for further research development are discussed in the discussion part.